High Follicle-Stimulating Hormone Level Associated With Risk of Rheumatoid Arthritis and Disease Activity - Zhang, Xianhui; Qiao, Pengyan; Guo, Qianyu; Liang, Zixie; Pan, Jie; Wu, Fengping; Wang, Xuexue; Zhang, Liyun (Frontiers in Endocrinology, 2022)
Background: The prevalence of rheumatoid arthritis (RA) has significant gender and age difference. The peak age of RA is consistent with the age of menopause, which is accompanied by a sharp increase in serum follicle-stimulating hormone (FSH) level. This study aims to identify the FSH levels in female RA patients and the relationship with diseases activity. Methods: In total, 79 female RA patients and 50 age-matched controls were included in our study. Serum sex hormones levels were measured using chemiluminescence. RA patients were grouped by FSH quartile. Disease activity and inflammatory marks were analyzed among groups. Results: Lower sex hormones and higher gonadotropin were found in RA patients. Serum FSH level was significantly higher in RA patients than in the age-match controls (57.58±15.94 vs. 43.11±19.46, p=0.025). Even after adjusting for age (OR: 1.071; 95%CI: 1.006-1.139; p = 0.031), luteinizing hormone (LH), estradiol (E), and testosterone (T) OR: 1.066; 95%CI: 1.003-1.133; p = 0.039), the OR were still more than one. RA patients in the higher quartiles had higher ESR, DAS28-ESR and DAS28-CRP (p<0.05) than the lowest quartile. Besides, menopause age was signiﬁcantly related with onset age in post-menopause RA patients (r = 0.432, p =0.008). Conclusion: High FSH appears to be a risk factor for RA and is positively associated with their disease activity. Early menopause might be an essential factor of RA.